The Impact of the BBNJ agreement’s EIA provisions on China: a comprehensive analysis under the SWOT-PEST framework - Fu, Jianbin; Liu, Weixian (Frontiers in Marine Science, 2025)
The Environmental Impact Assessment (EIA) provisions form a crucial part of the Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (the BBNJ Agreement) and are expected to have significant implications for States Parties. From a Chinese perspective, this study applies the SWOT-PEST analytical framework to examine the potential impacts of the BBNJ EIA rules on China.The findings reveal both opportunities and challenges across four dimensions: political, economic, social, and technological. Politically, China possesses certain policy and legal foundations, yet these are not fully developed, and while its international discourse power may expand, new regulatory barriers may arise. Economically, the healthy development of the marine economy supports the implementation of the new rules, however, in the short term, enterprises face multiple pressures such as rising costs and delayed returns, intensifying resource competition, while in the long run, this may facilitate their transformation and upgrading. Socially, despite existing gaps relative to international benchmarks, the engagement of diverse stakeholders provides a foundational basis for rule implementation, and although rising social pressures and adaptation costs present challenges, this also creates opportunities for multi-stakeholder development. Technologically, advancements in deep-sea technologies provide critical support for rule implementation while core technologies remain bottlenecked, facing threats from external technological barriers and simultaneously offering opportunities for cultivating marine technology expertise. Based on this analysis, the paper proposes potential strategies, including active participation in global ocean governance, advancement of deep-sea technologies, promotion of corporate transformation, and improvement of domestic legal frameworks